Open questions in the treatment of cancer pain: time for a strong evidence-based approach?. (January 2015) - Natoli, Silvia; Lazzari, Marzia; Dauri, Mario
<x xml:space="preserve">Abstract</x> Pain affects patients with cancer at any stage of their disease. Yet, it is not adequately treated in a significant percentage of cases. In 1986, the WHO proposed a three-step approach for the treatment of pain in cancer patients (from nonopioids to weak opioids to strong opioids, according to pain intensity) following the recommendations of an international group of experts. The application of the WHO strategy demonstrated that a clear and simple approach is of educational value and ensured worldwide dissemination. However, there is little evidence that the WHO approach is the best, and there are still several points to debate on the treatment of cancer pain.